2016
DOI: 10.4049/jimmunol.1600895
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of CD11c+CD163+ Adipose Tissue Macrophages through Upregulation of Intracellular 11β-HSD1 in Human Obesity

Abstract: Adipose tissue (AT) macrophages (ATMs) are key players for regulation of AT homeostasis and obesity-related metabolic disorders. However, the phenotypes of human ATMs and regulatory mechanisms of their polarization have not been clearly described. In this study, we investigated human ATMs in both abdominal visceral AT and s.c. AT and proposed an 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1)-glucocorticoid receptor regulatory axis that might dictate M1/M2 polarization in ATMs. The accumulation of CD11cCD16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 68 publications
4
56
0
Order By: Relevance
“…For example, in human abdominal subcutaneous adipose, ATMs accumulating in CLS expressed both CD11c and the commonly used M2 marker mannose receptor C type 1 (CD206), as well as both pro- and anti-inflammatory interleukins (IL-1β, IL-6, IL-8, and IL-10) (433). These results are further supported by Nakajima et al, who reported accumulation of ATMs expressing both CD11c and CD163, the latter of which is commonly associated with M2-like macrophages, in abdominal visceral and subcutaneous adipose of obese subjects (269). Shaul et al (350) also described a mixed M1/M2 phenotype in obese murine CD11c+ visceral ATMs, suggesting phenotypic and functional similarities between murine and human ATMs in obesity.…”
Section: Adipose Tissue Immune Populations In Cancer Development and supporting
confidence: 74%
“…For example, in human abdominal subcutaneous adipose, ATMs accumulating in CLS expressed both CD11c and the commonly used M2 marker mannose receptor C type 1 (CD206), as well as both pro- and anti-inflammatory interleukins (IL-1β, IL-6, IL-8, and IL-10) (433). These results are further supported by Nakajima et al, who reported accumulation of ATMs expressing both CD11c and CD163, the latter of which is commonly associated with M2-like macrophages, in abdominal visceral and subcutaneous adipose of obese subjects (269). Shaul et al (350) also described a mixed M1/M2 phenotype in obese murine CD11c+ visceral ATMs, suggesting phenotypic and functional similarities between murine and human ATMs in obesity.…”
Section: Adipose Tissue Immune Populations In Cancer Development and supporting
confidence: 74%
“…Early characterization of adipose tissue MF populations first described the obesity-induced appearance of proinflammatory MFs in conjunction with elevated levels of proinflammatory cytokines and chemokines such as TNF-a, IL6, and CCL2 (99,100). However, recent extensive profiling of adipose tissue MFs from adipose tissue of obese mice and humans has revealed a "mixed" pro-and anti-inflammatory phenotype (101)(102)(103)(104)(105)(106). Considering the complexity of phenotyping MFs by surface markers and expression profiling, the contribution of underlying metabolic parameters has the potential to inform us about MF phenotype and function in adipose tissue of obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…48 Interestingly, also CD11c + CD163 + ATMs were found to accumulate in fat of obese individuals and correlate with high BMI as well as the production of reactive oxygen species. 49 In addition to CD11c + CD206 + ATMs, it has been indicated that the population of CD11c + CD64 + ATMs also defines pro-inflammatory macrophages. 38 Additionally, the population of CD14 + CD16 + CD36 high ATMs has been shown to include highly phagocytic macrophages.…”
Section: Human Atm Markersmentioning
confidence: 99%